EFEITO DE DOIS ANTI-INFLAMATÓRIOS E UM ANTIOXIDANTE NA PREVENÇÃO DA SENSIBILIDADE CAUSADA PELO CLAREAMENTO DENTAL - Paula, Eloisa Andrade de (2013)
The tooth bleaching has a long history of tooth sensitivity (TS). This study aimed to determine the effect of different drugs, administered perioperatively, on tooth sensitivity and the degree of tooth whitening after in-office bleaching. A triple-blind,parallel design, randomized clinical trial were conducted. In the first experiment, the participants received a placebo or 400 mg ibuprofen every 8 h while in the second experiment, they were given a placebo or 60 mg etoricoxib every 24 h. In the third experiment, they received a placebo or 500 mg ascorbic acid every 8 h. In all experiments, the first dose of the drug was administered 1 h before in-office bleaching and taken for a period 48 h. The 35% hydrogen peroxide gel (Whiteness HP Maxx, FGM) was used in three 15-min applications for three groups following the manufacturer's directions. The in-office bleaching agent was refreshed every 15 min.Two bleaching sessions, with a one-week interval, were performed on each patient. The shade evaluation were performed before and 30-days, after bleaching with a Vita Easy Shade spectrophotometer and a Vita Classical’s visual shade guide. The tooth sensitivity was recorded on three scales: the five-point verbal rating scale, the 101 points scale, and the visual analogue scale, of and in different time points up to 1 h, 24 h, 48h after bleaching. The % of patients that reported TS at least once during treatment were evaluated by Fisher`s exact and the intensity of tooth sensitivity with Mann-Whitney test. Tooth color changes were evaluated by repeated ANOVA measures and t-test. There were no significant differences in the % of patients with tooth sensitivity and color change between the groups. The lowest tooth sensitivity was observed in the 400 mg ibuprofen group only up to 1 h post bleaching. The perioperative use of ibuprofen, etoricoxib and ascorbic acid per oral route was not able to avoid bleaching-induced tooth sensitivity according to the posology and dose used in this study. However, the 400 mg ibuprofen was able to reduce the intensity of tooth sensitivity up to 1 h post bleaching.